+0  
 
0
133
3
avatar+820 

If f(4) = -8, f'(4) = 3, g(4) = 3pi, and g'(4) = 4

 

and h(x)= 5 f(x)- 2/3 g(x)

 

find h'(x).

Landry  Sep 26, 2018

Best Answer 

 #2
avatar+7339 
+3

\(h(x)\,=\,5f(x)-\frac23g(x)\\~\\ \frac{d}{dx}[h(x)]\,=\,\frac{d}{dx}[5f(x)-\frac23g(x)]\\~\\ \frac{d}{dx}[h(x)]\,=\,\frac{d}{dx}[5f(x)]-\frac{d}{dx}[\frac23g(x)]\\~\\ \frac{d}{dx}[h(x)]\,=\,5\frac{d}{dx}[f(x)]-\frac23\frac{d}{dx}[g(x)]\\~\\ h'(x)\,=\,5f'(x)-\frac23g'(x)\)

 

That is the most you can say I think. smiley

hectictar  Sep 27, 2018
 #1
avatar+94100 
+2

Landry, are you sure this question is written properly?   frown

Melody  Sep 27, 2018
 #2
avatar+7339 
+3
Best Answer

\(h(x)\,=\,5f(x)-\frac23g(x)\\~\\ \frac{d}{dx}[h(x)]\,=\,\frac{d}{dx}[5f(x)-\frac23g(x)]\\~\\ \frac{d}{dx}[h(x)]\,=\,\frac{d}{dx}[5f(x)]-\frac{d}{dx}[\frac23g(x)]\\~\\ \frac{d}{dx}[h(x)]\,=\,5\frac{d}{dx}[f(x)]-\frac23\frac{d}{dx}[g(x)]\\~\\ h'(x)\,=\,5f'(x)-\frac23g'(x)\)

 

That is the most you can say I think. smiley

hectictar  Sep 27, 2018
 #3
avatar+820 
+1

I eventually got the answer. 

h(x)=5f(x)−23g(x)

 

d/dx[h(x)]=d/dx[5f(x)−23g(x)]

 

h ′(x)=d/dx[5f(x)]−d/dx[23g(x)]

 

h ′(x)=5d/dx[f(x)]−23d/dx[g(x)]

 

h ′(x)=5f ′(x)−23g ′(x)

 

h ′(4)=5f ′(4)−23g ′(4)

 

h ′(4)=5∗3−23∗4

 

h ′(4)=15−83

 

h ′(4)=453−83

 

h ′(4)=45−83

 

h ′(4)=373

Landry  Sep 27, 2018

9 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.